The influence of knowledge and attitudes of postpartum mothers in undergoing oukup therapy in the Nuaulu Inland Tribe based on the Health Belief Model; HBM - Sukardi, Trysna Ayu; Umamity, Syahfitrah; Rochmaedah, Siti (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Background: The postpartum period is the recovery period after childbirth until all the woman's reproductive organs recover before the next pregnancy. If the condition of the postpartum period is ignored, it will be one of the factors in the decline in the condition of the mother after childbirth, which will lead to death. The Naulu tribe is a native tribe of Seram Island, Central Maluku Regency, Maluku Province. Every transition in their lives will be marked by a traditional ceremony. Method: This research method is quantitative research with a one group pre test and post test only design approach. The research was carried out in the interior of the Nuaulu tribe, Maluku Province, for 3 months. Results: Postpartum mothers' knowledge in undergoing adequate therapy was seen as poor before being given education and after being given education, knowledge increased to good. Conclusion: Meanwhile, the attitude of postpartum mothers before being given education, the attitude of postpartum mothers was negative and after being given education, the attitude of postpartum mothers became average or the same.